Impact of Radiation Dose on Postoperative Complications in Esophageal and Gastroesophageal Junction Cancers - Kastelowitz, Noah; Marsh, Megan D.; McCarter, Martin; Meguid, Robert A.; Bhardwaj, Narine Wandrey; Mitchell, John D.; Weyant, Michael J.; Scott, Christopher; Schefter, Tracey; Stumpf, Priscilla; Leong, Stephen; Messersmith, Wells; et al. (Frontiers in Oncology, 2021)
Introduction: The impact of radiation prescription dose on postoperative complications during standard of care trimodality therapy for operable stage II-III esophageal and gastroesophageal junction cancers has not been established. Methods: We retrospectively reviewed 82 patients with esophageal or gastroesophageal junction cancers treated between 2004-2016 with neoadjuvant chemoradiation followed by resection at our institutiona single institution. Post-operative complications within 30 days were reviewed and scored using the Comprehensive Complication Index (CCI). Results were compared between patients treated with < 50 Gy and ≥ 50 Gy, as well as to published CROSS study neoadjuvant chemoradiation group data (41.4 Gy). Results: 29 patients were treated with < 50 Gy (range 39.6-46.8 Gy) and 53 patients were treated with ≥ 50 Gy (range 50.0-52.5 Gy) delivered using IMRT/VMAT (41%), 3D-CRT (46%), or tomotherapy IMRT (12%). Complication rates and CCI scores between our < 50 Gy and ≥ 50 Gy groups were not significantly different. Assuming a normal distribution of the CROSS data, there was no significant difference in CCI scores between the CROSS study neoadjuvant chemoradiation, < 50 Gy, or ≥ 50 Gy groups. Rates of pulmonary complications were greater in the CROSS group (50%) than our < 50 Gy (38%) or ≥ 50 Gy (30%) groups. Conclusions: In selected esophageal and gastroesophageal junction cancer patients, radiation doses ≥ 50 Gy do not appear to increase 30 day post-operative complication rates. These findings suggest that the use of definitive doses of radiotherapy (50-50.4 Gy) in the neoadjuvant setting may not increase post-operative complications.